Competitiveness of Indonesian ginger exports to Japan, Malaysia, and The United States - Mia Nurhidayati; Syafril Basri; Darmayuda Darmayuda (ARKA INSTITUTE, 2022)
The purpose of this study was to determine the competitiveness of Indonesian ginger in Japan, Malaysia, and the United States by analyzing the level of competitiveness, competitiveness position, and concentration of Indonesian ginger exports to Japan, Malaysia, and the United States. The research method used is the descriptive quantitative method. The period under study is 2012–2019, or eight years. The data analysis methods used are Revealed Comparative Advantage (RCA), Trade Specialization Index (ISP), and Market Concentration Index (IKP). The results of the RCA analysis of the competitiveness of Indonesian ginger exports to Japan, Malaysia, and the United States in 2012–2019 have comparative competitiveness 1. The average RCA scores were Japan (0.20), Malaysia (0.95), and the United States (0.07), respectively. In terms of competitiveness, Indonesia is an exporter country because ISPs have an average ISP value, namely Japan (0.93) in the maturation stage, Malaysia (0.61) in the expansion stage, and the United States (1.0) in the maturation stage. For market concentration, Indonesia has a relatively low IKP value, namely Japan (0.000024), Malaysia (0.000132), and the United States (0.000002), with a trade intensity value of (0-1).